Main design parameters to build acoustic maps by measurements in Uruguay - González, Alice Elizabeth (2025)
Uruguay is a small country in Latin America. It has 178.500 km2 and approximately 3,400,000 inhabitants. Its environmental legislation is still incomplete; for example, there has been a national act about noise pollution since 2004 but it has never been regulated. Thus, no national regulation on noise but only departmental Ordinances in each of its 19 Departments; in practice, 19 different regulations coexist on such a small surface. Noise maps are not mandatory neither in Uruguay nor in any of its Departments. The Research Group on Environmental Noise at Universidad de la República has developed a research project that seeks the best practical methodology to build noise maps through manual measurements. The fieldwork included the determination of the stabilization time of noise measurements, the comparison between long- and short-time measurements, the comparison between measurements taken at 1.20 m and 3.50 m, and the obtention of a national curve of highly annoyed people (% HA) with a basis in the field measurements and simultaneous survey carried out on site. In this article, we present the results of these works and the proposed methodology for building noise maps throughout the country.